Situation Report: Bulgaria, 9 January 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Decree on Measures to Increase Supply o Consumer Goods CC Calls for a Maximum Effort in Honor of Forthcoming 11th Party Congress Bulgarian Radio Increases Broadcast Time and Expands Program Variety